Knowledge and attitude toward the second round of COVID-19 vaccines among teachers working at southern public universities in Ethiopia - Getachew Asmare Adella (Taylor & Francis Group, 2022)
About 1.9 million people in Ethiopia have received a first dose of COVID-19 vaccine, which are given to frontline health care workers and university instructors through a campaign. After healthcare workers, teachers at all levels in Ethiopia are assumed to be at a higher risk of exposure to COVID-19. An institution-based cross-sectional study design was used. Simple random sampling was used to select participants. Data were collected using a structured, self-administered questionnaire. Logistic regression analysis was conducted for all variables, and a p-value < 0.05 at 95% CI was considered statistically significant. Overall, 60.8% and 79.7% of participants had good knowledge of and positive attitudes toward a second round of COVID-19 vaccines, respectively. Age (AOR = 1.51 [95% CI = 1.003-3.63]), profession (AOR = 1.402 [95% CI = 1.107-3.003]), work experience (AOR = 1.509 [95% CI = 1.151-2.283]), and chronic diseases (AOR = 2.142 [95% CI = 1.337-3.092]) were predictor variables for knowledge about the second round of COVID-19 vaccines. Sex (AOR = 1.386 [95% CI = 1.018-2.763]), marital status (AOR = 4.180 [95% CI = 2.397-6.989]), profession (AOR = 1.102 [95% CI = 1.008-3.123]), work experience (AOR = 1.211 [95% CI = 1.029-2.877]), and chronic diseases (AOR = 6.110 [95% CI = 4.892-10.661]) were predictor variables for attitudes toward a second round of COVID-19 vaccines. Generally, knowledge and attitudes toward the second round of COVID-19 vaccines among instructors were low. Thus, health education and communication are very crucial.